Adaptive Bilateral Texture Filter for Image Smoothing - Xu, Huiqin; Zhang, Zhongrong; Gao, Yin; Liu, Haizhong; Xie, Feng; Li, Jun (Frontiers in Neurorobotics, 2022)
The biggest challenge of texture filtering is to smooth the strong gradient textures while maintaining the weak structures, which is difficult to achieve with current methods. Based on this, we propose a scale-adaptive texture filtering algorithm in this paper. Firstly, the four-directional detection with gradient information is proposed for structure measurement. Secondly, the spatial kernel scale for each pixel is obtained based on the structure information, the larger spatial kernel for pixels in textural regions to enhance the smoothness, while the smaller spatial kernel for pixels on structures to maintain the edges. Finally, we adopt the Fourier approximation of range kernel, which reduces computational complexity without compromising the filtering visual quality. By subjective and objective analysis, our method outperforms the previous methods in eliminating the textures while preserving main structures, and also has advantages in structure similarity and visual perception quality.